Matrix metalloproteinases and tissue inhibitors in multiple myeloma: promote or inhibit? - Li, Yan-Ying; Zhang, Liu-Yun; Xiang, Yun-Hui; Li, Dan; Zhang, Juan (Frontiers in Oncology, 2023)
Matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) play a vital role in the pathogenesis of multiple myeloma (MM), especially for tumor invasion and osteolytic osteopathy. By breaking down extracellular matrix (ECM) components and releasing the proteins composing the ECM and growth factors, as well as their receptors, MMPs affect tissue integrity and promote cancer cell invasion and metastasis. A vital pathophysiological characteristic of MM is the progress of osteolytic lesions, which are brought on by interactions between myeloma cells and the bone marrow microenvironment. MMPs, certainly, are one of the fundamental causes of myeloma bone disease due to their ability to degrade various types of collagens. TIMPs, as important regulators of MMP hydrolysis or activation, also participate in the occurrence and evolution of MM and the formation of bone disease. This review focuses on the role of MMP-1, MMP-2, MMP-7, MMP-9, MMP-13, MMP-14, and MMP-15 and the four types of TIMPs in the invasion of myeloma cells, angiogenesis, osteolytic osteopathy, to offer some novel perspectives on the clinical diagnostics and therapeutics of MM. 1 migration and bone degeneration are both critically dependent on MMPs. In 1962, researchers discovered the first MMP from the tail of a tadpole, which can degrade collagen. In addition to the ability of MMPs to remodel the ECM, MMPs have been shown in recent years to play biological roles in cell signaling, immunological function, and transcriptional regulation(4). They function as regulators of tumor and host interactions because they can change the activity of several cytokines and growth factors(5).In recent decades, there have been a considerable number of studies on the role of MMPs in malignant tumors, but the majority of previous research mainly focused on the association of MMPs and solid tumor invasion, metastasis and angiogenesis, inflammatory response, and so on, whereas studies on the link between hematological malignancies and MMPs only account for a small part. Here, we mainly review the structures and functions of MMPs and TIMPs, what is more important, the role of MMPs and TIMPs in the progression of MM and the latest advances will be emphasized.